Comparative Drug Resistance of Mycobacterium abscessus and M. chelonae Isolates from Patients with and without Cystic Fibrosis in the United Kingdom - Broda, Agnieszka (American Society for Microbiology, 2013)
The isolation of rapidly growing mycobacteria (RGM), particularly Mycobacterium abscessus, from individuals with cystic fibrosis (CF) is associated with poor clinical outcome due to broad drug resistance and the difficulty of eradicating the organisms. Susceptibility testing is recommended to guide therapy. A disc diffusion method is used in the United Kingdom, whereas in the United States, the CLSI (Clinical and Laboratory Standards Institute) recommends the broth dilution method. The purpose of this study was to investigate whether the two methods produced comparable drug resistance profiles and to test the hypotheses that the disc diffusion method overscores resistance and that isolates of M. abscessus/M. chelonae from CF patients are more likely than those from non-CF patients to show drug resistance, as a result of CF patients' greater exposure to antibiotic therapy. A total of 82 isolates (58 M. abscessus and 24 M. chelonae isolates) were tested blindly against 15 antimicrobials by broth dilution and the disc diffusion method. Isolates tested by the broth microdilution showed high levels of resistance; susceptibility to amikacin, clarithromycin, tobramycin (only in M. chelonae), and cefoxitin (only in M. abscessus) was shown. Tigecycline results varied widely depending on which breakpoint was used. Agreement between methods for a few drugs (e.g., cefoxitin and amikacin) was poor. Although there were drug resistance differences between CF and non-CF isolates, these did not reach statistical significance. The CLSI method provided more robust breakpoints, standardization, and reproducibility. An analysis of the implementation of the CLSI method demonstrated ease of use and similar drug resistance findings for the two species.